Evaluation of the "Manggatang Utus" Village Movement Innovation Program in the Education Sector in Murung Raya Regency - Perdie Midel Yoseph; Agus Heruanto Hadna; Pande Made Kutanegara; Hakimul Ikhwan (International Journal of Science and Society, 2023)
Gerbang Desamu which is stand for “Gerakan Membangun Desa Manggatang Utus” is a policy innovation for the strategy program for accelerating village (kelurahan) development in Murung Raya District. The regional policy innovation at Gerbang Desamu is a grassroots innovation that holds the local wisdom values of the Huma Betang of the Dayak Tribes. The Gerbang Desamu Movement aims to accelerate the development of villages/kelurahans in Murung Raya Regency, especially in alleviating stupidity. This study aims to determine policy performance, policy efficiency, and local wisdom values in the policy innovations of the Gerbang Desamu program. This research focuses on exploring the production of knowledge and information on the innovative practices of Gerakan Desamu at the empirical and practical levels. This study is a mixed method research with a sequential explanatory mixed-method approach. The study results show that the performance of the Gerbang Desamu program has not been optimal. In terms of accessibility and reach to the broader community. This can be seen from the level of public understanding regarding the Gerbang Desamu policy innovation which is not evenly achieved. However, as a program, Gerbang Desamu is quite effective in achieving the program's objectives. Achievement of program objectives in the form of increasing the accessibility of community education, especially for children from underprivileged families. In addition, the internalization of local wisdom values in the Gerbang Desamu policy innovation is a unique success to be achieved in grassroots policy innovation. The values of togetherness, honesty, equality, and tolerance are local wisdom values that underlie grassroots policy innovations in the Gerbang Desamu program.